Modalities of diagnosis and treatment of liver trauma - Tarek Fathi Afifi Elsaid; Ahmad Hussein Khalil; Ayman Salah; Mostafa Abdelhameed Soliman (Cairo : Tarek Fathi Afifi Elsaid, 2014)
The liver is the most frequently injured intraabdominal solid organ following trauma despite its relatively protected location. Due to its anatomical location, severe liver injuries usually lead to exsanguinating haemorrhage which is the most common cause of death. This is a retrospective and prospective study included A total of 100 patients with liver injuries presented to (1- Accident and Emergency department, Kasr Alaini hospital, Faculty of Medicine, Cairo University. 2- Accident and Emergency department, New Kasr Alaini teaching hospital, Faculty of Medicine, Cairo university. 3- hepato pancreato biliary unit, freeman hospital, Newcastle upon Tyne, UK) between January 2011 - July 2013. The age of the patients ranged from 9 years to 56 years. The patients included were 78 males and 22 females.The most frequent cause of liver trauma was blunt trauma (50%) mainly RTA
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of General Surgery
Issued also as CD
Keywords: Liver; Non operative management; Trauma